Apotek Hidup Untuk Masyarakat di Desa Lobung - Nashran Azizan; Sarika Adawiyah; Maulana Arafat Lubis (Khidmat Almujtamae: Jurnal Pengabdian Masyarakat, 2023)
Life Pharmacies are becoming popular because they will impact health and income. A living pharmacy is a collection of herbal medicines grown through natural processes. This article aims to explain from the manufacturing process to the benefits obtained. The Living Pharmacy being developed is in Lobung Village. Previously, there had never been a Living Pharmacy. The development of the Living Pharmacy is carried out by utilizing land to grow plants that can be used as natural medicines to benefit people's health. The aim of creating the Living Pharmacy is to provide new knowledge to the public regarding how to plant and use wild medicinal plants to increase immunity or as an effort to maintain health. The results of creating a Living Pharmacy in Lobung Village, precisely next to the village head's house, can increase knowledge of the local community in growing plants that can be used as herbal medicine, often called herbal medicine.